Breast Cancer Myths, Mysterious Miracles and Mistrust among Rural Womenfolk in Sarawak - Melissa Lim, Siaw Han; Fitri Suraya, Mohamad; Chew, Keng Sheng; Nafeesa, Mat Ali; Yolanda, Augustin (West Asia Organization for Cancer Prevention (WAOCP), 2025)
Background: Sarawak hospitals report high rates of advanced cancer among women in remote rural areas. Cultural beliefs, low awareness, socio-economic challenges, geographical barriers, and the lack of specialist cancer care contribute to late diagnoses, particularly in breast cancer, exacerbating disparities in access to timely treatment. Objective: This study aimed to explore cultural beliefs, barriers, and healthcare access challenges influencing breast cancer awareness and screening among Sarawak’s indigenous and rural communities. Methods: This qualitative study explores how rural Sarawakian women perceive breast cancer and their access to healthcare. Twenty women from three main geographical terrains in Borneo-coastal, riverine, and highland areas participated in the study. After informed consent was obtained, semi-structured interviews were conducted. Data was coded and thematically analyzed to identify cultural nuances affecting their knowledge. Results: The study found a strong link between cancer and negative beliefs rooted in sociocultural backgrounds. Myths varied, but most associated cancer with death, a fatalistic culture relying on spiritual faith for healing. Participants delayed seeking medical help until “the pain is unbearable,” often using oils and herbs first. Lack of knowledge and lack of access to information about cancer are two main findings from the study. Although the majority of the respondents were not equipped with adequate information, they expressed interest in learning about breast screening programs and attending breast cancer awareness campaigns. Conclusion: The findings will be used to design behavioral intervention modules to educate rural Sarawak populations about the importance of breast self-examination (BSE) practices, early detection, and screening.